ROLE OF OLIVE OIL IN CANCER PREVENTION - GAP Ratih Pradnyandari; IGN Sri Wiryawan (Universitas Udayana, 2014)
Cancer is the second leading cause of death in the United States. From this fact showshow ferociously the disease if not treated well. The emergence of this disease is causedby various factors, but often caused by damage to the structure of DNA and othermolecular structures by a reactive oxygen species (ROS). Early prevention that can beimplemented, is to improve the lifestyle and diet that contains a substance that canprotect our body cells from damage caused by ROS. These molecules calledantioxidants. Therefore, antioxidants are often called reducing agents (thiol orpolyphenols). Olive oil is the one of the exogenous antioxidants have many benefitsespecially polyphenols that have chemo preventive effects on several types of cancer,and can inhibit the process of carcinogenesis by several mechanisms such as inhibitionof DNA synthesis in the process, reducing the production of ROS, regulate cell cycle,regulate proliferation and survival mechanisms of cells.